Study on the blast resistance of concrete beams reinforced with ultra-high-molecular-weight polyethylene (UHMWPE) fibers. Issue 4 (March 2020) - Zhang, Zhao; Yan, Luhui; He, Zhiyang; Ma, Jiajun; Wang, Huiming
Abstract: Experiments and numerical simulations were performed to investigate the blast resistance of concrete beams reinforced with ultra-high-molecular-weight polyethylene (UHMWPE) fibers under close-in blast loads. The blast tests were carried out on fiber- reinforced concrete beams with a volume content of 0.7% at three scaled distances (i.e., 0.36, 0.40, and 0.47 m/kg 1/3 ) and the damage results were compared with the characteristics of normal reinforced concrete beams. The results show that the UHMWPE fibers can decrease the damage degree of the beams, hinder the generation and development of cracks, and prevent spalling on the back surface, indicating that the blast resistance of UHMWPE-fiber-reinforced concrete beams is better than that of normal reinforced concrete beams with the same strength grade. Due to the addition of fibers, the improvement in the damage resistance to blast loads at the bottom surface of the beam is better than that at the top surface. A 3D blast-test model was established and calculated using the LS-DYNA software. A numerical study of the extended scaled distances was carried out to determine the change law of the damage features based on it. When the scaled distance is greater than 0.41 kg/m 1/3, the damage mode of the beam begins to change from the mode of large damage at the bottom and small damage at the top to the mode involving large damage at the top and small damage at the bottom.